THU0033 The chemokine mip-1alpha in rheumatoid arthritis – possible significance on inflammation and anaemia. (1st June 2001) - Kullich, WC; Pöllmann, G; Neff, H; Klein, G
Abstract : Background: Chemokines play a key role in modulating leukocyte functions at sites of inflammation. In rheumatoid arthritis (RA) an enhancement of the chemokine macrophage inflammatory protein-1alpha (MIP-1a) was observed and may be indicative for inflammatory processes. 1 In addition to its proinflammatory activities several lines of evidence indicate that MIP-1a modulates the proliferation of hematopoietic progenitor cells. 2 Anaemia is a common feature of active rheumatoid arthritis. Very little information on the significance of MIP-1a on the pathogenesis of anaemia in RA is available. Objectives: Basing on theoretical, haematological and immunological data, the chemokine MIP-1a was to be determined about its importance in RA concerning the activity of inflammation and the development of anaemia. Methods: 84 patients (18 male, 66 female) with rheumatoid arthritis (ACR criteria) were included to detect inflammatory processes and anaemia. White and red blood cell count, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), serum iron and the rheumatoid factor were assessed by routine laboratory methods. MIP-1a, serum amyloid A (SAA) and transferrin receptor (TfR) were measured by solid phase enzyme immunoassay; erythropoietin (EPO) and neopterin by radioimmunoassay techniques. Results: High MIP-1a levels were accompanied by increased parameters of inflammation (SAA, CRP, ESR). Patients with RA and anaemia showed significantly higher MIP-1a levels than those without anaemia (p < 0.03). However, high MIP-1a levels together with decreased serum iron were not associated with increased EPO levels. It might be of importance that patients with high MIP-1a levels in parallel with anaemia and activation of inflammation had a twofold frequency of disability pension compared to RA patients without anaemia. Conclusion: The enhanced expression of MIP-1a in RA is indicative of the inflammatory activation. Moreover besides the regulation of inflammatory processes this chemokine may influence the pathogenesis of anaemia in RA. References: Koch AE, Kunkel SL, Harlow LA, et al . Macrophage inflammatory protein-1 alpha. A novel chemotactic cytokine for macrophages in rheumatoid arthritis. J Clin Invest. 1994;93: 921–8 Su SB, Mukaida N, Wang JB, Zhang Y, Takami A, Nakao S, Matsushima K. Inhibition of immature erythroid progenitor cell proliferation by macrophage inflammatory protein-1a by interacting mainly with a C-C chemokine receptor, CCR1. Blood 1997;90(2):605–11